2022
DOI: 10.1002/hep4.1955
|View full text |Cite
|
Sign up to set email alerts
|

Variants in mitochondrial amidoxime reducing component 1 and hydroxysteroid 17‐beta dehydrogenase 13 reduce severity of nonalcoholic fatty liver disease in children and suppress fibrotic pathways through distinct mechanisms

Abstract: Genome‐wide association studies in adults have identified variants in hydroxysteroid 17‐beta dehydrogenase 13 (HSD17B13) and mitochondrial amidoxime reducing component 1 (MTARC1) as protective against nonalcoholic fatty liver disease (NAFLD). We aimed to test their association with pediatric NAFLD liver histology and investigate their function using metabolomics. A total of 1450 children (729 with NAFLD, 399 with liver histology) were genotyped for rs72613567T>TA in HSD17B13, rs2642438G>A in MTARC1, and rs7384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
(135 reference statements)
0
32
1
Order By: Relevance
“…In the article, a comprehensive study on the influence of a common variant of the mitochondrial amidoxime reducing component 1 (gene: MTARC1; protein: mARC1) on nonalcoholic fatty liver disease (NAFLD) in children is presented. [ 1 ]…”
Section: Figurementioning
confidence: 99%
“…In the article, a comprehensive study on the influence of a common variant of the mitochondrial amidoxime reducing component 1 (gene: MTARC1; protein: mARC1) on nonalcoholic fatty liver disease (NAFLD) in children is presented. [ 1 ]…”
Section: Figurementioning
confidence: 99%
“…Although the precise role and physiological function of MARC1 are unknown, it has been proposed that this lipid phenotype may hint at a possible physiological mechanism by which MARC1 could participate in NAFLD [ 12 , 30 ]. Accumulating evidence has associated the occurrence of hypertriglyceridemia as a central factor in the progression of the liver, metabolic, and cardiovascular disease [ 27 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the rs2642438-A allele has been associated with higher triglyceride levels, lower HDL-c, and low liver enzyme levels [ 9 , 11 ]. It has been shown that MARC1 deficiency can protect against cirrhosis [ 11 ] and decrease the severity of nonalcoholic fatty liver disease (NAFLD); however, the mechanism involved is unclear [ 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…
To the editor, We read with great interest the manuscript from Struwe et al [1] and their insightful comment on our recent article. [2] Their X-ray crystallography studies on mARC1 (encoded by MTARC1) illustrate two important general points: the limitation of in silico modeling and the challenge of understanding human variants.In silico modeling of protein structure (and protein variants) is based on assumptions of amino acid interactions and how they combine in higher-level protein folding. Despite enormous progress being made in the field, [3] there is no replacement for the gold standard of X-ray crystallography, as used by Struwe et al For this reason, structural biology will continue to be indispensable for understanding mechanisms and drug discovery.Together, these data suggest that it will be challenging to elucidate the mechanism through which this variant protects against liver disease.
…”
mentioning
confidence: 99%
“…To the editor, We read with great interest the manuscript from Struwe et al [1] and their insightful comment on our recent article. [2] Their X-ray crystallography studies on mARC1 (encoded by MTARC1) illustrate two important general points: the limitation of in silico modeling and the challenge of understanding human variants.…”
mentioning
confidence: 99%